Recovery of heat-injured listeria innocua - Miller, Fátima A. (2010)
Listeria innocua was subjected to thermal inactivation and the extent of heat-injured cells was quantified. Cultures were heated in liquid medium for different times, using temperatures in the range of 52.5 to 65.0 °C, and plated on Tryptic Soy Agar with 0.6% yeast extract (TSAYE) used as non-selective medium and on TSAYE plus 5% NaCl (TSAYE+NaCl) and Palcam agar with selective supplement (Palcam agar) as selective media. The difference observed in counts in non-selective and in selective media gave an indication of cell injury during the heat treatment. D- and z- values were calculated for all conditions considered. For each temperature, D-values obtained using non-selective recovery procedures were higher than the ones obtained using the two selective media. When comparing the selective media, it can be concluded that Palcam agar allowed recovery and growth of thermally injured cells and so it was less inhibitor than TSAYE+NaCl. Another important result was the influence of temperature on the degree of cellular injury. As temperature increases, the degree of heat-injured cells also increases, and consequently concern has to be taken with the temperature and the counting medium used in food processing studies. The results of this work clearly demonstrated that selective media used for Listeria monocytogenes enumeration/detection might not be suitable for the recovery of heatinjured cells, which can dangerously underestimate the presence of this foodborne pathogen.